2013
DOI: 10.1177/1090820x12472695
|View full text |Cite|
|
Sign up to set email alerts
|

The Lower Nasal Base: An Anatomical Study

Abstract: Currently, most rhinoplasty surgeons focus their analysis and operative techniques on the upper nasal base, with its alar cartilages. They tend to minimize the lower nasal base, composed of the columellar base, nostril sills, and alar lobules. The requisite operative techniques are often considered ancillary techniques. In this article, the authors describe anatomical composition of the columellar base, nostril sill, and alar lobule; discuss the presence of a distinct lower nasal base; and reevaluate the nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 25 publications
(20 reference statements)
2
47
0
2
Order By: Relevance
“…Many of the facial muscles affect the nose and specifically the lower nasal base [23]. Although we did not evaluate the smile in this study, many surgeons consider the depressor septi nasi as the main contributor to a plunging nasal tip.…”
Section: Discussionmentioning
confidence: 98%
“…Many of the facial muscles affect the nose and specifically the lower nasal base [23]. Although we did not evaluate the smile in this study, many surgeons consider the depressor septi nasi as the main contributor to a plunging nasal tip.…”
Section: Discussionmentioning
confidence: 98%
“…Kamburoğlu et al [4] set the marginal incision 3-4mm from the skin rim regardless the cartilage can be some millimeters ahead. A cadaveric study sets the variable distancies that can be observed among patients [5]. Direct palpation is technically a challenge because of the expertise the surgeon needs to have.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal incisions are described by many manners: while some authors use metrical distances [3,4], others use anatomical landmarks [5], or direct palpation [6,7], which is difficult in thick skin patients. In this paper, we describe a new anatomical landmark that appears after tumescence rhinoplasty technique and how this fold affects to the surgery in terms of reducing operative time.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, many of these muscles affect the nose and specifically the lower nasal base. 9 It is implausible that this perceived plunge could be attributed to a single muscle. Specifically, the actions of the depressor septi nasi (DSN) and, less commonly, the levator labii superioris alaeque nasi (LLSAN) have been attributed to the tip that "plunges" on smiling.…”
Section: The Muscles Of the Nasal Base And Their Effect On Smilementioning
confidence: 99%
“…11 The LLSAN has a labial and alar portion the insertion of which is into the upper lip as well as the nasal alae and accessory cartilages at the level of the pyriform aperture, respectively. 9 It is an obvious target when trying to correct the smiling deformity.…”
Section: Contribution Of Llsan To the Movement Of The Lower Third Of mentioning
confidence: 99%